Mohs micrographic surgery: a study of 83 cases Cirurgia micrográfica de Mohs: estudo de 83 casos - Flavianne Sobral Cardoso Chagas; Bruno de Santana Silva (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Mohs micrographic surgery can achieve high cure rates in the treatment of skin cancer and remove a minimum of healthy tissue. OBJECTIVES: To characterize patients undergoing Mohs micrographic surgery and study issues related to the number of surgical stages. METHODS: A descriptive, retrospective, cross-sectional study was conducted in a micrographic surgery reference center for the period of 2004 to 2010. Data was collected from medical records of 79 patients (83 surgeries). RESULTS: We studied 43 women and 36 men. The mean age was 57.5 ± 14,6 years. Skin types II and III were the most frequent, accounting for 41% and 36.1%, respectively. The most frequent tumor was the basal cell carcinoma (89.1%), and the solid subtype was the most common (44.6%), followed by sclerodermiform histological subtype (32%).The most frequent location was the nasal region (44.6%). The large majority of the operated tumors were recurrent lesions (72.7%). Half of the tumors measured 2 cm or more. In 68.7% of the cases two or more surgical stages were necessary for the removal of the tumors. The observation period was 2 or more years in 75% of the tumors. There was 01 post-Mohs recurrence and 02 patients had metastases during the observation period (both with squamous cell carcinoma). CONCLUSION: The findings coincide with those of the literature, recurrent tumors and tumors larger than 2cm needed more surgical stages for their removal, although there was no statistic difference (p=0,12 and 0,44 respectively). FUNDAMENTOS: A cirurgia micrográfica de Mohs é capaz de alcançar altas taxas de cura no tratamento do câncer de pele e remover o mínimo possível de tecido saudável. OBJETIVOS: caracterizar os pacientes submetidos à cirurgia micrográgica de Mohs e estudar aspectos relacionados ao número de fases cirúrgicas. MÉTODOS: trata-se de estudo observacional, transversal e descritivo realizado em serviço de referência para cirurgia micrográfica no período de 2004 a 2010. Foram revisados os prontuários de 79 pacientes (83 cirurgias). RESULTADOS: Foram avaliados 43 mulheres e 36 homens. A média de idade foi 57,5 ± 14,6 anos. Os fototipos II e III foram os mais frequentes, respondendo por 41% e 36,1% respectivamente. O tumor mais freqüente foi o carcinoma basocelular (89,1%), sendo o subtipo sólido o mais frequente (44,6%), seguido pelo esclerodermiforme (32%). A localização mais freqüente foi a nasal (44,6%). A grande maioria dos tumores operados eram recidivados (72,7%). Metade dos tumores mediam 2 cm ou mais. Foram necessárias duas ou mais fases cirúrgicas em 68,7% dos tumores para sua remoção. O tempo de acompanhamento foi igual ou superior a 2 anos em 75%. Houve 01 recidiva pós-Mohs e 02 pacientes apresentaram metástases durante o estudo (ambos carcinomas espinocelulares). CONCLUSÕES: Os achados coincidem com os da literatura, sendo que tumores recidivados e maiores que 2cm necessitaram de mais fases cirúrgicas para sua completa remoção, apesar de não haver diferença estatística (p=0,12 e 0,44, respectivamente).